Comparative Analysis of Compatibility Influence on Invigorating Blood Circulation for Combined Use of Panax Notoginseng Saponins and Aspirin Using Metabolomics Approach - Sun, Zongxi; Wu, Huichao; Wu, Yali; Wang, Chenglong; Wang, Yu; Hu, Shaonan; Du, Shouying (Frontiers in Pharmacology, 2021)
The combined use of Panax notoginseng saponins (PNS)-based drugs and aspirin (ASA) to combat vascular diseases has achieved good clinical results. In this study, the superior efficacy was observed via the combined use of PNS and ASA on acute blood stasis rats, and untargeted metabolomics was performed to holistically investigate the therapeutic effects of coupling application and its regulatory mechanisms. The combined use of PNS and ASA exhibited better improvement effects to reduce the evaluated hemorheological indicators (whole blood viscosity, plasma viscosity, platelet aggregation, and fibrinogen content) in the blood stasis rats versus single-use of PNS or ASA at the same dose. The combined use of both drugs was the most effective application method as shown by the relative distance in partial least-squares discriminant analysis score plots. Twelve metabolites associated with blood stasis were screened as potential biomarkers and were mainly involved in amino acid metabolism, lipid metabolism, and energy metabolism. After coherently treated with PNS and ASA, the altered metabolites could be partially adjusted to closer to normal levels than single-use. The collective results revealed that PNS could cooperate with ASA to treat blood stasis and provided a scientific explanation for the superior efficacy of their combined use.